THE MODERNIZATION OF THE SYSTEM OF IMPLEMENTATION OF ARTICLES 81 AND 82 OF THE TREATY OF THE EUROPEAN COMMUNITY FROM THE SPANISH PERSPECTIVE - Calvo Caravaca, Alfonso Luis; Universidad Carlos III de Madrid (Editorial Pontificia Universidad Javeriana y Facultad de Ciencias Jurídicas, 2004)
In this paper we are going to deal with the impact of the community antitrust modernisation in Spain. the present paper starts describing the spanish competition system and goes on to analyse different aspects of the impact of community modernisation. from an institutional point of view spanish legal system is well positioned to implement the new european model of control of the practices against the competition but an important group of problems are now without solution.